History of art - Host Woldemar Janson (1913- (harry N. Abrams, 1991)
The book refers both to the evens that make the history of art, and to the scholarly discipline that deals with these evens. It presents 557 magnificent color illustrations, 625 rich duotones and line drwings, four-color portfolio, Key Moniments in this book, that features critical turning points in West art, illustrations of major works in situ, an updated text that throughout reflects the most current scholarship and critical thinking, reorganized sections on modern painting, sculpture, and architecture, the distinction between Neoclassicism and Romanticism. The modern architecture begins with Frank Lloyd Wright, while its antecedents, including the Chicago School and Art Nouveau